Hear Us Out : Conversations with Gay Novelists. - Canning, Richard (Between Men~Between Women: Lesbian and Gay Studies., 2010)
The author of the acclaimed Gay Fiction Speaks brings us new interviews with twelve prominent gay writers who have emerged in the last decade. Hear Us Out demonstrates how in recent decades the canon of gay fiction has developed, diversified, and expanded its audience into the mainstream. Readers will recognize names like Michael Cunningham, whose Pulitzer Prize?winning novel The Hours inspired the hit movie; and others like Christopher Bram, Bernard Cooper, Stephen McCauley, and Matthew Stadler. These accounts explore the vicissitudes of writing on gay male themes in fiction over the las.